2005
DOI: 10.1002/pbc.20619
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib is effective against juvenile pilocytic astrocytoma in vitro

Abstract: Based on these preclinical data, gefitinib may be a suitable salvage chemotherapy drug to explore further in those patients with JPA who have recurred after primary chemotherapy. Of interest, it appears that the anti-tumor effect of gefitinib in JPA cell-cultures may be mediated through a pathway other than EGFR inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…One study showed that gefitinib was able to inhibit rhabdoid cell growth in vitro by inhibition of EGFR phosphorylation [80]. Another study performed on juvenile polycytic astrocytoma (JPA), a brain tumor with good prognosis after gross total resection, demonstrated that the inhibitory effect of gefitinib was independent of EGFR expression [81].…”
Section: Preclinical Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…One study showed that gefitinib was able to inhibit rhabdoid cell growth in vitro by inhibition of EGFR phosphorylation [80]. Another study performed on juvenile polycytic astrocytoma (JPA), a brain tumor with good prognosis after gross total resection, demonstrated that the inhibitory effect of gefitinib was independent of EGFR expression [81].…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…4 c-Kit-positive NB cell lines sensitive (growth inhibition 30 -80%)c-Kit-negative NB cell line GI-CA-N was slightly affected, suggesting other imatinib targets operate in regulating NB proliferation Sharp decrease of c-Kit phosphorylation could be demonstrated[58] in vitro/in vivoGrowth inhibition of NB cells in vitro and in a NB xenograft model in SCID miceSuppression of PDGFR and c-Kit phosphorylation Inhibition of angiogenesis by down-regulation of VEGF expression[57] in vitro/in vivo Imatinib tumor concentration in NB tumors independent of administered dose and no correlation with antitumor effectNo clear-cut correlation between the levels of expression for imatinib-responsive targets and in vitro/in vivo sensitivity[63] Ewing Sarcoma (EWS) in vitro 8 EWS cells resistant in vitro despite expression of imatinib sensitive tyrosine kinases[66] in vitroDown-regulation of c-kit phosphorylation and dose response inhibition of EWS cell proliferation (IC50: 12-15 micro M)No induction of apoptosis by 10 M Increased antitumor effect of chemotherapy by inhibiting the proliferative rate of EWS cells by 15-20% in doxorubicine and by 15-36% in vincristine, and increased apoptotic rate by 15 and 30% when exposed to the same drugs[67] in vitro/in vivoInterference with growth of all EWS cell lines tested in vitro and in vivo c-kit expression and phosphorylation in EWS cells Oral administration (every 12 hours for 5-7 days) on primary tumor growth in EWS xenografts in SCID/bg mice [68] Neuroectodermal tumors (EWS, PNET and NB) in vitro/in vivo Decrease in cell proliferation and increase of cell apoptosis in a concentration-and time-dependent manner Inhibition to some extent independent of c-Kit inhibition since cells remained sensitive to SCF stimulation Tumor volume significantly reduced in mice Apoptosis independent on caspase activation Accumulation of reactive oxygen species resulting in cell death [61] Gefitinib Neuroblastoma (NB) in vitro 40% to 50% reduction in the number of SY5Y and NLF cells after exposure to 0.5 M gefitinib Inhibition of auto-phosphorylation of EGFR by EGF in NB cell lines at 0.01 M Blocked phosphorylation of AKT, but not MAPK, in NLF cells at 0.1 M [78] Rhabdoid tumor in vitro/in vivo Inhibition of EGFR-phosphorylation and cell growth Induction of apoptosis at high concentrations in vitro Cytostatic effect on established xenografts of radiotherapy [80] Juvenile pilocytic astrocytoma (JPA) in vitro Inhibition of proliferation in five JPA short-term primary cell-cultures (IC-50:1.6 -9.6 M)EGFR protein and mRNA expression undetectable[81] …”
mentioning
confidence: 99%
“…In preclinical studies, gefitinib treatment was associated with growth inhibition and increased apoptosis in human cancer cell lines, and antitumor effects against xenografts of human tumors [ 606 , 607 ]. Gefitinib was shown to inhibit proliferation in juvenile PA primary cell cultures with an IC 50 determined between 1.6 and 9.6 µM [ 608 ]. In addition, this compound was shown to inhibit invasion and metastasis of intratibial OS xenografts via inhibition of macrophage receptor interacting serine-threonine kinase 2 (RIPK2) [ 609 ].…”
Section: Kinases As Druggable Targets—evidence and Limitationsmentioning
confidence: 99%
“…Recent molecular genetic studies have found that the short arm of chromosome 7, which contains the epidermal growth factor receptor (EGFR) gene, undergoes amplification likely resulting in the increased expression of EGFR seen in PA with dissemination compared to those without [30]. Thus, EGFR inhibitors may prove useful as an adjuvant treatment for disseminated PAs in the near future [31]. …”
Section: Discussionmentioning
confidence: 99%